Ilmu Pegangan Hidup Seorang Muslim dalam Kesenian Kentrung Blora, Jawa Tengah - Firlie Ni'mah Husnayain; Sutiyono Sutiyono (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2019)
Blora’s kentrung has changed as a performing arts so we can see its performance at big stage not only at small events. It becomes an art icon. The government strives for this art to remain sustainable, by bringing it up as an entertainment art for the people. Its educative values include the teaching of life philosophy in line with Walisongo teachings in a chronicle story supplemented with advice, prayer, and pantun in performances that entertain the audience. It is called